(untitled) (Journal of the College of Education for Women, 2021)
This present work is concerned with one of the syntactic issues that has been researched by many linguists, grammarians, and specialists in Islamic studies, the estimated answer to a condition. However, this topic is researched this time by examining Imam Al-Qurtbi’s opinions in interpreting related ayas from the holly Quraan in his book (Collector of Quranic Rules) or its transliteration (Al-Jami’ Li Ahkam Al-Quran). Such a step involves commenting on, tracking what Al-Qurtbi said in this regard, discussing it from the points of view of other grammarians, and judging it accordingly, taking into account the apparent surface structures of the examples collected. To achieve this objective, the inductive analytical approach has been adopted in the analysis by tracing Al-Qurtbi’s various views in interpreting the Quranic verses. One of the most important conclusions of this study is that Al-Qurtubi was a carful interpreter of such linguistic issues, as his analysis was characterized by being highly intellectual and mature. Concerning the estimation of the answer to a condition, the study has concluded that Al-Qurtubi was concerned with the applied aspect of the concepts of interpretive and superficial structures, specifically when he estimated the answer to a condition in each presented verse.